(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The paper looks at the state’s internal and external image and the definitions of “concept” and “image” are clarified. The issues under discussion include the state image components, specifics of image building, specifics of country’s image on the domestic and foreign markets, and the PR goals in the building of state’s image.